2018
DOI: 10.1177/1129729817747536
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urea recirculation and thermodilution for monitoring of vascular access in patients undergoing hemodialysis

Abstract: Urea recirculation is better predictor of vascular access dysfunction than thermodilution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…(14) Urea recirculation, which calculated access flow from inducing urea recirculation by reversing bloodline had a high sensitivity and specificity in detecting needed for intervention. However, this method works well for low blood flow, whereas insensitive at high flow (12,15) Color Doppler ultrasonography can evaluate the access flow and identify the stenosis sites in the AVF (16) but, is operator dependent and time-consuming. Several studies have shown the benefit of noninvasive monitoring tools for detecting vascular access stenosis (12,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…(14) Urea recirculation, which calculated access flow from inducing urea recirculation by reversing bloodline had a high sensitivity and specificity in detecting needed for intervention. However, this method works well for low blood flow, whereas insensitive at high flow (12,15) Color Doppler ultrasonography can evaluate the access flow and identify the stenosis sites in the AVF (16) but, is operator dependent and time-consuming. Several studies have shown the benefit of noninvasive monitoring tools for detecting vascular access stenosis (12,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Urea recirculation, which calculated access ow from inducing urea recirculation by reversing bloodline had a high sensitivity and speci city in detecting needed for intervention. However, this method works well for low blood ow, whereas insensitive at high ow [13,16] Additionally, ultrasound dilution and urea circulation methods are strongly related to blood pressure and it might be better to calculate a ratio between the measured access ow and blood pressure.…”
Section: Introductionmentioning
confidence: 99%